Penegakan Hukum Pidana Terhadap Pelanggaran Hak Cipta di Era Digital Berdasarkan Undang-Undang Hak Cipta di Indonesia - Rahman Zulkarnaen (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2026)
The development of digital technology has brought a significant impact on the increase of copyright infringement in Indonesia. This study aims to analyze criminal law enforcement against copyright violations in the digital era and to identify the challenges faced in its implementation. The research method used is normative juridical with a statutory approach and a conceptual approach, supported by a literature study from various primary and secondary legal sources. The results show that forms of copyright infringement in the digital era are increasingly diverse, including digital piracy, re uploading content without permission, illegal distribution through digital platforms, as well as the misuse of technologies such as artificial intelligence and deepfake. Although Law Number 28 of 2014 concerning Copyright has explicitly regulated criminal sanctions, the effectiveness of law enforcement still faces various obstacles, such as difficulties in digital evidence, the anonymity of perpetrators, and jurisdictional limitations due to the cross border nature of the internet. In addition, the low level of public legal awareness further exacerbates the situation. Therefore, adaptive regulatory reform, strengthened cross sector collaboration, and increased public legal literacy are required to support more effective law enforcement. This study is expected to contribute to the development of legal policies related to copyright protection in the digital era.